Roman Rule and Civic Life: Local and Regional Perspectives Proceedings of the Fourth Workshop of the International Network Impact of Empire (Roman Empire, c. 200 B.C. - A.D. 476), Leiden, June 25-28, 2003 - de Ligt, L.; Hemelrijk, E.A; Singor, H.W (Impact of Empire, 2004)
Ancient history: to c 500 CE